(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The history of the study of proverbs, their development and characteristics is indicated. Based on the analysis, the role of intercultural communication in the study of proverbs is revealed, the national-cultural aspects of French and Uzbek proverbs are revealed, and their structure, meanings, word order and lexical units are clarified.